El artículo 41 de la Constitución y el especial requisito de procedibilidad en el caso del delito de enriquecimiento ilícito - Nakazaki Servigón, Cesár Augusto (Revista de Derecho, 2019)
The paper deals with legal requirements procedure in case of the crime of illicitenrichment. Through a correct interpretation of article 41 of the Constitution shallbe determined that it is a requirement in case of such crime that the public criminalproceedings are to be instituted only by the General Attorney, contrary to national jurisprudencehad maintained until “Case of Congress member Cecilia Chacon de Vettori”.
Keywords: Illicit enrichment; Constitution; requirements procedure; criminal proceedings